Pathogenic CD8 T Cells in Multiple Sclerosis and Its Experimental Models - Huseby, Eric S.; Huseby, Priya G.; Shah, Shivanee; Smith, Rebecca; Stadinski, Brian D. (Frontiers in Immunology, 2012)
A growing body of evidence suggests that autoreactive CD8 T cells contribute to the disease process in Multiple Sclerosis (MS). Lymphocytes in MS plaques are biased toward the CD8 lineage, and MS patients harbor CD8 T cells specific for multiple central nervous system (CNS) antigens. Currently, there are relatively few experimental model systems available to study these pathogenic CD8 T cells in vivo. However, the few studies that have been done characterizing the mechanisms used by CD8 T cells to induce CNS autoimmunity indicate that several of the paradigms of how CD4 T cells mediate CNS autoimmunity do not hold true for CD8 T cells or for patients with MS. Thus, myelin-specific CD4 T cells are likely to be one of several important mechanisms that drive CNS disease in MS patients. The focus of this review is to highlight the current models of pathogenic CNS-reactive CD8 T cells and the molecular mechanisms these lymphocytes use when causing CNS inflammation and damage. Understanding how CNS-reactive CD8 T cells escape tolerance induction and induce CNS autoimmunity is critical to our ability to propose and test new therapies for MS.